Human Capital, Effort, and the Sexual Division of Labor - Becker, Gary S. (Journal of Labor Economics, 1985)
Increasing returns from specialized human capital is a powerful force creating a division of labor in the allocation of time and investments in human capital between married men and married women. Moreover, since child care and housework are more effort intensive than leisure and other household activities, married women spend less effort on each hour of market work than married men working the same number of hours. Hence, married women have lower hourly earnings than married men with the same market human capital, and they economize on the effort expended on market work by seeking less demanding jobs. The responsibility of married women for child care and housework has major implications for earnings and occupational differences between men and women.